LaeA Controls Virulence and Secondary Metabolism in Apple Canker Pathogen Valsa mali - Feng, Yaqiong; Yin, Zhiyuan; Wu, Yuxing; Xu, Liangsheng; Du, Hongxia; Wang, Nana; Huang, Lili (Frontiers in Microbiology, 2020)
Apple Valsa canker is a destructive disease caused by the ascomycete Valsa mali and poses a serious threat to apple production. Toxins synthesized by secondary metabolite biosynthetic gene clusters (SMBGCs) have been proven to be crucial for pathogen virulence. A previous study showed that V. mali genome contains remarkably expanded SMBGCs and some of their genes were significantly upregulated during infection. In this study, we focus on LaeA, a known regulator of secondary metabolism, for its role in SMBGC regulation, toxin production, and virulence of V. mali. Deletion of VmLaeA led to greatly reduced virulence with lesion length reduced by 48% on apple twigs. Toxicity tests proved that toxicity of secondary metabolites (SMs) produced by VmLaeA deletion mutant (ΔVmlaeA) was markedly decreased in comparison with wild-type (WT). Transcriptomic and proteomic analyses of WT and ΔVmlaeA indicated that a portion of transporters and about half (31/60) SMBGCs are regulated by VmLaeA. Function analysis of eight gene clusters including PKS7, PKS11, NRPS14, PKS16, PKS23, PKS31, NRPS/PKS33, and PKS39 that were differentially expressed at both transcriptional and translational levels showed that four of them (i.e., PKS11, PKS16, PKS23, and PKS31) were involved in pigment production and NRPS14 contributed to virulence. Our findings will provide new insights and gene resources for understanding the role of pathogenicity-related toxins in V. mali.